Failure mechanism and soil deformation pattern of soil beneath interfering square footings - Arash Alimardani Lavasan; Mahmoud Ghazavi (Numerical Methods in Civil Engineering)
In this research, the variation of ultimate bearing capacity, failure mechanism and deformation pattern of soil beneath two closely square footings have been studied using numerical methods. It is assumed that the adjacent footings are constructed on the surface of sand. The presented numerical analyses are based on explicit-finite-difference code, FLAC3D. The elasto-plastic behavior of soil is modeled by using Mohr-Coulomb failure criteria along with associated flow rule for the soil. The reliability of constructed numerical simulation is investigated using available data on interfering footings. In addition, a large scale test is performed on two closely spaced square footings. Failure mechanism and deformation pattern are compared with the results obtained from numerical data. A pretty well agreement is observed between numerical and experimental results. The numerical analyses have shown a significant influence of interference on the failure mechanism and deformation pattern of the soil as well as the footing ultimate bearing capacity.